PENGARUH PENGGUNAAN TEKNIK SQ3R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN - Asri, Ratih Permata; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Universitas Negeri Padang, 2016)
ABSTRAKÂ This research aims to describe the effect of the use of techniques SQ3R the level of reading comprehension class VII SMP Negeri 1 Koto XI Tarusan. The type of this research was quantitative research done using experimental design. There are three results of the research are (1) reading comprehension without using techniques SQ3R class VII SMP Negeri 1 Koto XI Tarusan was more fairly and grades LdC with average 68,80, (2) reading comprehension with using techniques SQ3R class VII SMP Negeri 1 Koto XI Tarusan was good and grades B with average 83,80, and (3) based on the t-test, the alternative hypothesis (H1) was gained at the significant phase 95% and degrees of freedom (df) = (n1+n2)-2 because tcount> t-table (7,42> 1,67).Â Kata kunci : pengaruh, teknik SQ3R, dan membaca pemahaman